Personal Finance Knowledge of Young People and it’s Impact on Economic Health in India - Sathyapriya, M; Nandagopal, R (Journal of Contemporary Research in Management (JCRM), 2017)
This research work investigates personal financial knowledge and its impact on economic health by examining the relationships among the factors including Savings and Investments, Inflation and Effect of Interest Rate. The research model is examined using a survey approach on the young people in India. In the paper, Frequencies, Mean, Anova and SEM Model were used in carrying out analysis. The study identified that individual’s need knowledge beyond the fundamental financial concepts. This is to be expected, any saving plan requires some numeracy, the ability to calculate present values, and an understanding of the advantages of starting to save early in life. It is also acknowledged that the rapidly growing body of economic health is bound with the young people’s personal financial knowledge. This paper could be useful references for researchers who are interested in personal financial management in a context of emerging economies like India.